Potential economic impacts of technological and organisational innovations in intermodal access to major passenger terminals - Francisco J. Tapiador; Jordi Martí-Henneberg (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
This report deals with the potential economic impacts of innovations such as smart ticketing and instantaneous access to rail and modal connection information schedules. First, the qualitative role of TOIs (technological and organizational innovations) is explored within the framework of intermodality. Secondly, a simple, quantitative, parametric model is described. The model is then used to analyze the impact of TOIs on rail demand, accessibility and passenger welfare under the assumption of bounded rationality. Providing that the model captures the major processes in play, the results will show the potential effects of policy choices and technological innovations both on their own and in a combined form, thus enabling discussion of their relative merits and synergies. An analysis of quantitative results shows that the effect is positive, highly non-linear, and prone to cumulative effects due to far-reaching impacts related, for instance, to the economics of climate change.
Keywords: 330